Tell what you want but do not irritate me: a senior perspective about advertising - Loureiro, S. M. C. (Journal of Promotion Management, 2018)
This study provides an understanding of the underlying processes and attitudes toward advertising while watching in TV and YouTube. We intend to contribute to better understand what could lead senior consumers to avoid advertising. The aims are to (i) analyze the relationship between drivers to ad avoidance among senior viewers and (ii) compare the perceptions about those drivers between TV advertising and YouTube advertising among senior viewers. A sample of 214 senior viewers provided data to test the hypotheses. Findings reveal that irritation seems to be the crucial factor that lead consumers to avoid whacking advertising. A negative attitude toward advertising and skepticism do not mediate the effect between advertising irritation and avoidance. The article also provides managerial implications and suggestions to further research.